Factors related to the social competence of adolescent students with orthopedic impairments - De Los Reyes, Ivy B. (2007)
Most individuals with physical impairments encounter mobility problems, restrictions, out casting and stereotyping behaviors from other people. This study was undertaken to determine the social competence level of 28 adolescent students with Primary Orthopedic Impairments studying at the National Orthopedic Hospital School for Crippled Children Main and Annex Campuses. Data were obtained by administering the Student and Teacher Form Social Skills Rating System, Social Questionnaire to high school students with orthopedic impairments. Results showed no significant difference in the subjects' social competence level between the 2 schools surveyed. Teachers' perception on students vary in both campuses. Females and Teacher Rated Externalizing and Internalizing problematic behaviors were found to be significantly associated with one another.
"July 2007."
Thesis (M.A. Educational Technology)--University of the Philippines Diliman.
Keywords: National Orthopedic Hospital School for Crippled Children; Children with disabilities -- Education -- Social aspects -- Philippines; Children with disabilities -- Services for -- Philippines; Special education teachers -- Philippines; Special education -- Philippines